Pengembangan Media Pembelajaran Fun Thinkers Book Rainbow pada Mata Pelajaran PPKN Kelas IV Sekolah Dasar - Ita, Ita Novianti; Bukman Lian; Kiki Aryaningrum (Study program PGSD FKIP Universitas Bung Hatta, 2024)
This research aims to produce a fun thinkers book rainbow learning media product for Civics lessons on ethnic and religious diversity in my country for fourth grade elementary school students that is valid, practical and effective. This research and development uses the ADDIE model development procedure (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research were class IV students at SD Negeri 5 Palembang with a total of 17 students. Criteria for the quality of fun thinkers book rainbow media in Civics lessons material on ethnic and religious diversity in my country which can be seen from the validation results of media experts, material experts and language experts. Media validity results based on media experts were 83.95% categorized as very valid, validation by material experts was 82.57% categorized as very valid, validation by language experts was 86.69% categorized as very valid, validation by educators was 89.90% categorized as very valid , the student questionnaire response of 83% was categorized as very practical, the teacher response questionnaire of 94% was categorized as very practical, then the results of the effectiveness trial were 82.35% categorized as very effective. Based on the data that has been presented, the Fun Thinkers Book Rainbow learning media for Civics subjects, material on ethnic and religious diversity in my country, is very suitable for use. Keywords: Fun Thinkers Book Rainbow Learning Media